Gambaran Nilai Hematokrit Pada Pasien Demam Berdarah Dengue Di Rsud 45 Kuningan - Pipin Supenah; Muhammad Ibnu Ubaidillah; Ikhwani Ikhwani; Diyanah Alifia Ramadhan (Universitas Muhamadiyah Manado, 2021)
Dengue Hemorrhagic Fever is still one of the disease problems in Indonesia today. The first case of DHF in Indonesia itself occurred in 1986 in the city of Surabaya, this disease continues to increase and spread throughout Indonesia, which causes all parts of Indonesia to be at risk of being infected with this disease. Dengue fever or dengue fever is an infectious disease caused by the dengue virus and is transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes. This disease is one type of health disorder that interferes with everyone's productivity and is one of the infectious diseases that often causes outbreaks and causes death. This study aims to determine the hematocrit value in dengue hemorrhagic fever patients and what percentage of the hematocrit value in dengue hemorrhagic fever patients is in accordance with the normal value standard with descriptive research methods and examination methods using a hematology analyzer. For data analysis using the SPSS program, the K Independent Samples Test with a sig value of 0.000 was carried out on 33 blood samples obtained from dengue hemorrhagic fever patients in a regional hospital 45 kunngan purposively. The results showed that there were differences in the hematocrit value in patients with dengue hemorrhagic fever. The results of the examination of the hematocrit value of dengue hemorrhagic fever patients showed an increase in the hematocrit value of 12 people with a percentage of 36.40%, a decrease of 6 people with a percentage result of 18.20% and for normal numbers as many as 15 people with a percentage result of 45.50 %